QUALITY AND SAFETY OF SMOKED CATFISH (Aries talassinus) USING PADDY CHAFF AND COCONUT SHELL LIQUID SMOKE - Fronthea Swastawati (JOURNAL OF COASTAL DEVELOPMENT, 2008)
The purpose of this research was to determine quality of smoked catfish (Arius thalassinus) using paddy chaff and coconut shell liquid smoke. The fish were divided into two groups; then processed using paddy chaff and coconut shell liquid smoke. All of the smoked catfish samples were subjected to chemical, microbiological and organoleptic analyses. The result indicated that moisture content of the paddy chaff smoked cat fish was 48.72%; a little bit lower than coconut shell smoked cat fish that was 51.27%. TPC on paddy chaff treatment was 53.33 CFU/gr; higher than coconut shell treatment that was 46.67 CFU/gr. Organoleptic value of smoked cat fish treated by paddy chaff liquid smoke was 8.26 and coconut shell was 8.22. It was found that benzo(α)pyrene content in the paddy chaff liquid smoke was not detected and in the coconut shell liquid smoke was 11.351 ppm. Examination of t-test Independent sample to the TPC and moisture content showed P>0.05.